Centro de rehabilitación neurológica: Barrio Samper Mendoza (2017)
The project find as objective to complement existing applications, since in the area there are health, cultural, administrative and judicial facilities which have no relationshipin a functional and much less urban context, Since very densified area in areas such as Las Americas lacks public space. Restructuring of the area and the new proposal is intended to strengthen the health system, likewise the urban context giving an order and proper functionalty. The large floating population present in the day does not generate more traffic problems vehicular and pedestrian, another objective is to improve and give you moreefficiency Meredi greater University hospital, for this arises a center of neurological rehabilitation that are intended to strengthen hospital specialty giving it a plus to the health system, for this arises not only use specified in rehabilitation you will also need areas like; observation, emergency, outpatient, surgery and hospitalization.